2016
DOI: 10.1001/jamaoncol.2015.4482
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Younger Age and Targetable Genomic Alterations and Prognosis in Non–Small-Cell Lung Cancer

Abstract: Importance NSCLC in the young is a rare entity and the genomics and clinical characteristics of this disease are poorly understood. In contrast, young age at diagnosis has been demonstrated to define unique disease biology in other cancers. Here we report on the association of young age with targetable genomic alterations and prognosis in a large cohort of NSCLC patients. Objective To determine the relationship between young age at diagnosis and both the presence of a potentially targetable genomic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
234
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(266 citation statements)
references
References 47 publications
25
234
7
Order By: Relevance
“…The search for drug-targetable mutations in most studies showed that young patients exhibit a high mutation rate, especially for EGFR and EML4 ALK [7,20,33,34]. In our study, the most frequent mutations concerned KRAS (23%) and EML4 ALK (15%).…”
Section: Discussionsupporting
confidence: 51%
“…The search for drug-targetable mutations in most studies showed that young patients exhibit a high mutation rate, especially for EGFR and EML4 ALK [7,20,33,34]. In our study, the most frequent mutations concerned KRAS (23%) and EML4 ALK (15%).…”
Section: Discussionsupporting
confidence: 51%
“…In their cohort, those younger patients (less than 40 years old) are more likely to be never smokers (67%), and older patients (more than 60 years old) are less likely to be never smokers (22%). Under multivariable analysis, the association between EGFR mutations and age was not significant [26]. ALK rearrangements may explain at least in part why younger patients had a lower positive EGFR mutation rate in this study.…”
Section: Discussionmentioning
confidence: 90%
“…[3][4][5]. However, some investigators reported that advanced age might represent a risk factor for more aggressive and/or more rapidly progressive RCC [6].…”
Section: Introductionmentioning
confidence: 99%